Rewrite the following expressions: 27^1/2 * 27^1/4 .(1 point)

27^1/8

27^3/4

4√27

3√27

1 answer

To rewrite the expression \(27^{1/2} \cdot 27^{1/4}\), you can use the property of exponents which states that when multiplying like bases, you add the exponents:

\[ 27^{1/2} \cdot 27^{1/4} = 27^{(1/2 + 1/4)} \]

First, find a common denominator to add \(1/2\) and \(1/4\):

\[ 1/2 = 2/4 \]

So,

\[ 1/2 + 1/4 = 2/4 + 1/4 = 3/4 \]

Thus, the expression simplifies to:

\[ 27^{3/4} \]

So, \(27^{1/2} \cdot 27^{1/4} = 27^{3/4}\).

Among the options given, the answer is:

27^{3/4}.